2023
DOI: 10.3390/hydrology10070156
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Mitigation of Fecal Bacteria Exports from a Coastal North Carolina Watershed

Abstract: Urban runoff from the Boat House Creek watershed was suspected as a main delivery mechanism for fecal indicator bacteria (FIB) to the lower White Oak River Estuary in coastal North Carolina, but the dominant source of waste (animal or human) was unknown. Water samples from eight locations within the watershed were collected approximately monthly for two years for enumeration of Escherichia coli (E. coli), enterococci, physicochemical characterization, and microbial source tracking analyses. Concentrations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Primers and probes for bacterial human indicator detection were BacHum Rev 5 ′ -CGCTACACCAC GAATTCCG-3 ′ , BacHum Fwd 5 ′ -CGCGGTAATACGGAGGATCC-3 ′ , BacHum LNA Probe 5 ′ -/56-FAM/AAGTTT+GC+GG+C+T+CAAC/3IABkFQ/-3 ′ (IDTDNA, Coralville, IA, USA). Similar protocols have been used in prior studies [21,22] to help identify bacteria sources. Stream samples from inlets 1 and 2 were collected during late summer (September) and early winter (December) of the project period.…”
Section: Water Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Primers and probes for bacterial human indicator detection were BacHum Rev 5 ′ -CGCTACACCAC GAATTCCG-3 ′ , BacHum Fwd 5 ′ -CGCGGTAATACGGAGGATCC-3 ′ , BacHum LNA Probe 5 ′ -/56-FAM/AAGTTT+GC+GG+C+T+CAAC/3IABkFQ/-3 ′ (IDTDNA, Coralville, IA, USA). Similar protocols have been used in prior studies [21,22] to help identify bacteria sources. Stream samples from inlets 1 and 2 were collected during late summer (September) and early winter (December) of the project period.…”
Section: Water Analysesmentioning
confidence: 99%
“…However, prior research [61] has shown that check dams can reduce runoff volumes by 17% and increase hydraulic residence times by 29% or more. Other research [62] reported that implementation of check dams in drainageways helped to reduce the total volume and dynamic flows and the stormflow transport of pollutants, such as fecal indicator bacteria [21].…”
Section: Mitigation Effortsmentioning
confidence: 99%
See 1 more Smart Citation